Paralyzed by shock: the portfolio formation behavior of peer-to-business lending investors - Gregor Dorfleitner; Lars Hornuf; Martina Weber (Review of Managerial Science, 2022)
We examine investor behavior on a leading peer-to-business lending platform and identify an investment mistake that we refer to as default shock bias. First, we find that investors stop investing in new loans and cease diversifying their portfolio after experiencing a loan default. The default shock significantly worsens the risk–return profile of investors' loan portfolios. The defaults investors experience are often not beyond what would have been expected from the information that was provided by the platform ex ante. Second, investment experience on the platform is related to better investment decisions in general, but it does not reduce the default shock bias. These findings have important implications not only for the behavioral finance literature but also more generally for new forms of Internet-based finance.
Keywords: G21; G23; L31; M14; 650; Behavioral finance; Investment bias; Peer-to-business lending; Crowdlending; Risk-adjusted return on capital; Diversification